2001
DOI: 10.1677/joe.0.1700197
|View full text |Cite
|
Sign up to set email alerts
|

In vitro free radical scavenging capacity of thyroid hormones and structural analogues

Abstract: It was reported that thyroid hormones decreased Cu 2+ -induced low-density lipoprotein (LDL) oxidation in vitro. Here, we investigated free radical scavenging capacities of thyroid hormones (3,5,3 -tri-iodo-L-thyronine (T 3 ), thryoxine (T 4 ) and 3,3 ,5 -tri-iodo-L-thyronine (rT 3 )) and structural analogues (L-thryonine (T 0 ), 3,5,3 -tri-iodothyroacetic acid (TA 3 ) and 3,5,3 ,5 -tetraiodothyroacetic acid (TA 4 )), using three different models of free radical generation. T 0 , T 3 and TA 3 slowed down produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 34 publications
3
19
1
Order By: Relevance
“…Thyroid hormones and structural analogues were reported to protect LDL from oxidation induced by non-cellular pro-oxidant agents (Hanna et al 1993, Chomard et al 1998, Oziol et al 2001 and by endothelial cells (Hanna et al 1995). In the present study, we found that these compounds also reduced macrophage-induced LDL oxidation in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Thyroid hormones and structural analogues were reported to protect LDL from oxidation induced by non-cellular pro-oxidant agents (Hanna et al 1993, Chomard et al 1998, Oziol et al 2001 and by endothelial cells (Hanna et al 1995). In the present study, we found that these compounds also reduced macrophage-induced LDL oxidation in a concentration-dependent manner.…”
Section: Discussionsupporting
confidence: 69%
“…Transition metal ions like Fe 2+ may favour macrophage ROS generation and LDL radical attack (Xing et al 1998, Yuan & Brunk 1998. If the radical scavenging capacity of thyroid compounds was predominant outside the cells, T 3 and TA 3 ought to have decreased LDL lipid peroxidation more than T 4 and rT 3 , as previously found during AAPH-induced LDL oxidation (Oziol et al 2001); however, we found the contrary here. Since T 0 had no antioxidant effect here and considering the antioxidant capacity of Ham's F-10, as discussed above, it may be proposed that T 0 does not enter the macrophages whereas the other compounds do, and/or that these compounds act on macrophage cellular mechanisms whereas T 0 does not.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations